Bullying victimization and mental health before and during the COVID-19 pandemic - Farrell, Ann H.; Brittain, Heather; Krygsman, Amanda; Vaillancourt, Tracy (Frontiers in Child and Adolescent Psychiatry, 2024)
Bullying victimization is associated with numerous mental health difficulties yet studies from early in the COVID-19 pandemic revealed significant decreases in bullying victimization but significant increases in mental health difficulties for many children and adolescents. It is unclear whether the decrease in bullying victimization early in the pandemic translated to weaker associations between bullying victimization and mental health difficulties. Using a population-based design, we examined whether the correlations between bullying victimization and mental health difficulties were significantly weaker in magnitude during the COVID-19 pandemic compared to before the pandemic in a sample of 6578 Canadian students in grades 4-12. Students were randomly assigned to report on their bullying and mental health experiences either during the school year before the pandemic or the school year during the pandemic. Only students who reported experiences of victimization were included in the present study as questions on mental health were specifically on difficulties experienced due to victimization. As expected, overall bullying victimization and mental health difficulties were significantly correlated before and during the pandemic, but correlations were significantly weaker in magnitude during the pandemic for girls and secondary students. Significant decreases in correlation magnitude were also found predominately for general, verbal, and social forms of bullying victimization, but not for physical and cyber victimization. Among students who reported victimization, we also found significantly lower means for mental health difficulties and most forms of bullying victimization during the pandemic compared to pre-pandemic. Findings indicate a strong coupling of bullying victimization and mental health difficulties, particularly before the pandemic, and the need to reduce these associations to improve the well-being of children and adolescents.